2006
DOI: 10.1161/01.hyp.0000236551.00191.61
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Birth Weight and Blood Pressure Is Robust, Amplifies With Age, and May Be Underestimated

Abstract: Abstract-Data on the early life origins of adult hypertension have been widely reported: however, recent research shows that the strength of association between small size at birth and higher blood pressure weakens as study size increases.In this article, we retest the association between birth weight and systolic blood pressure in a large cohort, examine whether age interacts with birth weight to predict blood pressure, and explore reasons why birth weight-blood pressure associations tend to weaken with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
96
4
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 28 publications
(42 reference statements)
10
96
4
2
Order By: Relevance
“…Although the referenced studies (9,10) only evaluated male offspring and some rodent studies have demonstrated sex differences in programmed hypertension (24,25), a majority of such studies ultimately reveal programmed hypertension in both genders (26 -32). This is consistent with human epidemiologic studies revealing similar relations between birth weight and cardiovascular death or hypertension in men and women (33)(34)(35). Although we are not aware of any fetal programming models that have demonstrated sex-specific programming of coronary physiology, our inability to perform meaningful subgroup analysis within the context of the present study may hamper the generalization of our results to other model systems.…”
Section: Discussionsupporting
confidence: 83%
“…Although the referenced studies (9,10) only evaluated male offspring and some rodent studies have demonstrated sex differences in programmed hypertension (24,25), a majority of such studies ultimately reveal programmed hypertension in both genders (26 -32). This is consistent with human epidemiologic studies revealing similar relations between birth weight and cardiovascular death or hypertension in men and women (33)(34)(35). Although we are not aware of any fetal programming models that have demonstrated sex-specific programming of coronary physiology, our inability to perform meaningful subgroup analysis within the context of the present study may hamper the generalization of our results to other model systems.…”
Section: Discussionsupporting
confidence: 83%
“…The median birth weight of the SGA newborns in our study corresponds to the 1.6th percentile defining a relatively homogeneous cohort of growth-restricted neonates. The majority of epidemiologic studies have correlated just LBW with the risk for hypertension (28). One may expect an even more pronounced effect if only infants with proven intrauterine compromise could have been included in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies by Barker and colleagues (1), showing that size at birth was related to adult chronic disease, extended this interest to intrauterine programming. Blood pressure (BP) is strongly and directly associated with mortality from cardiovascular disease (7), and the evidence for associations of low birth weight with adverse outcomes in later life is robust for BP (8) [although this has been disputed (9)]. In addition, there are strong cohort effects for secular changes in BP providing evidence for a role of early exposures (10,11).…”
mentioning
confidence: 99%